A Comparative Evaluation of Blood Glucose and Salivary Glucose Levels in Diabetic Patients –A Pilot Study - G. , Anuradha; Muthukrishnan, Arvind; Priya Veeraraghavan, Vishnu (International Journal of Psychosocial Rehabilitation, 2020)
Diabetes mellitus is a metabolic disorder characterized by hyperglycemia because of absolute or relative insufficiency of insulin secretion and/or concomitant resistance to the metabolic action of insulin on target tissues. According to the Diabetes International Federation report, in 2017 there were 451 million people with diabetes worldwide, and it is expected to increase to 693 million by 2045. (1) India is among the top few countries with an increased burden of diabetes, with its prevalence increasing from 26.0 million in 1990 to 65.0 million in 2016 (2).